WISDOM survey: attitudes and behaviors of physicians toward vulvar and vaginal atrophy (VVA) treatment in women including those with breast cancer history. Issue 2 (February 2019) - Kingsberg, Sheryl A.; Larkin, Lisa; Krychman, Michael; Parish, Sharon J.; Bernick, Brian; Mirkin, Sebastian
Abstract: Objective: To evaluate and compare physicians' behaviors and attitudes regarding vulvar and vaginal atrophy (VVA) treatment in menopausal women, including women with breast cancer, using an internet-based survey. Methods: The WISDOM survey queried obstetricians and gynecologists (OB/GYNs) and primary care physicians (PCPs) with 23 multipart questions assessing behaviors and attitudes towards VVA treatment. Results: Of 2, 424 surveys sent, 945 (39%) responded and 644 (27%) were completed. Of the menopausal women seen by OB/GYNs and PCPs, 44% to 55% reported having VVA symptoms. Physicians prescribed VVA treatments primarily because of effectiveness. Only 34% of OB/GYNs and 17% of PCPs felt comfortable prescribing VVA therapies to women with a personal history of breast cancer. In general, the most common VVA treatment recommended by all was prescription therapy (49%; with or without other therapies) in the form of US Food and Drug Administration-approved vaginal estrogen creams. More OB/GYNs (72%) than PCPs (47%) disagreed that VVA was best treated with over the counter than prescription products. Out-of-pocket cost and fear of risks associated with estrogens were believed to be the main barriers for why women choose not to get treated and why they discontinue treatment. Conclusions: More OB/GYNs than PCPs prescribed VVA treatment, especially vaginal estrogens, for menopausal women, but both groups generally had similar attitudes and behaviors regarding VVA treatment. Physician comfort was low when prescribing to women with a history of breast cancer, despite women's health medical societies supporting vaginal estrogen use in women with a history of estrogen-dependent breast cancer who were unresponsive to nonhormonal therapies when offered in consultation with their oncologist.